“Based on the True Story of”: Political Filmmaking and Analogical Thinking - Staiger, Janet (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2010)
“Based on the True Story of” considers how reception studies contributes to determining what constitutes effective political filmmaking and the lessons these films offer to encourage political allegiances. Prior work has indicated that filmmakers need to provide narrative frames to insure their preferred views are accessible to audiences, that excessive emotional appeals can backfire, that conspiracy narratives are more accepted if the narratives argue for complicated webs of power structure, and that markers of authorial subjectivity provide space for spectators to negotiate the material. Here analogical thinking – finding resemblances of one or more features between events in the text and the historical past – is studied for docudramas. Using the reception of Good Night, and Good Luck (2005), the essay argues two further hypotheses that also involve analogical thinking : (1) reviewers expect audiences to seek lessons and explicitly engage with a film's assumed message about contemporary politics, and (2) reviewers often reposition the lessons into other generic narrative formula which have heroes and villains.